1999
DOI: 10.1111/j.1469-7793.1999.0801n.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the odour‐induced response in frog olfactory receptor cells

Abstract: which has been suggested to reflect progressive inactivation of voltagegated Na¤ channels during the odour-induced depolarisation (Trotier, 1994). While whole-cell patch clamp recordings from olfactory receptor cells have demonstrated that the odourinduced receptor current follows a steep dose-response relation (Firestein et al. 1993), the relationship between the receptor current and action potential firing has hitherto received relatively little attention (Trotier, 1994). The adaptation of the response to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
110
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(125 citation statements)
references
References 50 publications
9
110
4
1
Order By: Relevance
“…A sustained background stimulus should therefore produce a much stronger and more persistent depolarization in these cells compared with WT OSNs. At a certain concentration of the background odor, this stimulus should lead to complete inactivation of voltage-gated Na ϩ channels, causing depolarization block thereby preventing the cells from eliciting action potentials to test odors (26,27). Because of the threshold of the voltage dependence of Na ϩ channel inactivation, the extent of this impairment should depend strongly on relatively small changes in concentration of the background odor, consistent with the results shown in Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A sustained background stimulus should therefore produce a much stronger and more persistent depolarization in these cells compared with WT OSNs. At a certain concentration of the background odor, this stimulus should lead to complete inactivation of voltage-gated Na ϩ channels, causing depolarization block thereby preventing the cells from eliciting action potentials to test odors (26,27). Because of the threshold of the voltage dependence of Na ϩ channel inactivation, the extent of this impairment should depend strongly on relatively small changes in concentration of the background odor, consistent with the results shown in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…4A). This finding suggests that the ability of OSNs to adapt to sensory stimulation extends the working range of odor detection to higher concentrations (26), thus optimizing discrimination capacity. What is the molecular basis for the failure of CNGA4 Ϫ/Ϫ mice to detect an odor stimulus in the presence of the same or related background stimuli?…”
Section: Discussionmentioning
confidence: 88%
“…For example, as in vertebrate OSNs (37,44), the steady-state receptor current in Drosophila Or-expressing OSNs during adaptation can reach less than 20% of the transient peak response. Also similarly to vertebrate OSNs (37,38), adaptation reduced the sensitivity and slowed the response kinetics of Drosophila Or-expressing OSNs, consistently with LFP studies using SSR (24). Furthermore, we found that adaptation in Drosophila Or-expressing OSNs was mediated by the Ca 2+ influx during odor responses, as is that in vertebrate OSNs (36,38).…”
Section: Discussionsupporting
confidence: 66%
“…In vertebrate OSNs, several mechanisms have been proposed, including the desensitization of transduction channels, phosphorylation of odorant receptors, inhibition of adenylyl cyclase, and potentiation of phosphodiesterase activity (37,38,45). Recent molecular genetic studies have revealed, however, that adaptation in vertebrate OSNs is more complex than previously understood (46,47).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation